Given two functions, we can combine them in such a way so that the outputs of one function become the inputs of the other. ... 3, right parenthesis first and then substitute that result into f f ff to find our answer. ..... Problem 1 ..... end{aligned} (h∘g)(x)=h(g(x))=(g(x))2−2(g(x))=(x+4)2−2(x+4)=x2+8x+16−2x−8=x2+6x+8Define.
Answer:
$2.47
Step-by-step explanation:
The cabinetmaker would have paid $13.31 for everything.
Answer:
x = 5
Step-by-step explanation:
Answer:
I want to say the answer is No, I'm sorry if I am wrong.